Pastoralism ... - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
now virtually non-existent north of the 200mm isohyet (rainfall line). The drought years have ruined much of the grazing land, and because so many men have left the area there is insufficient manpower to draw up water from the wells. From Mauritania...